PENGEMBANGAN MEDIA PEMBELAJARAN PUZZLE PADA MATA PELAJARAN MATEMATIKA MATERI BANGUN DATAR TERHADAP MINAT BELAJAR SISWA KELAS III - Antik Estika Hader; Ana Novitasari; Sindy Novri Septia (STKIP Subang, 2025)
This research is motivated by the lack of student focus on learning, students tend to be silent listening to teacher explanations, and rarely use learning media. Monotonous learning makes students bored and unenthusiastic so that students' interest in learning mathematics is still low. Therefore, it is necessary to develop a learning media that can increase students' interest in learning, one of which is by using Puzzle learning media. This study aims to determine the validity, practicality and effectiveness of puzzle learning media. This study uses the Research and Development (R&D) method with the 4D development model (Define, Design, Develop and Disseminate). The subjects in this study were third-grade students of SDN 13 Koto Baru. The results of the puzzle learning media assessment on the validation test by three validators produced an average value of 87% categorized as valid. The practicality test by teachers and students produced an average value of 95.12% categorized as practical in terms of use. The effectiveness test is based on the results of the student learning questionnaire with an average of 87.8% was categorized as effective.